2009
DOI: 10.5088/atl.2009.31.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Stages of gonadal development and mean length at first maturity of wild females of white shrimp (Litopenaeus schmitti - DECAPODA, PENAEIDAE) in southern Brazil

Abstract: The stages of gonadal development for the female of white shrimp (Litopenaeus schmitti (Burkenroad, 1936)) were characterized based on histological analysis. Four stages (immature, developing, ripe and spawned) were determined according to the structure and arrangement of cells in the ovary. Each stage corresponds macroscopically to a characteristic color, except stages I (immature) and IV (spawned), in which colors are very similar and can be distinguished only microscopically. The chromatic scale varies from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 9 publications
3
10
1
5
Order By: Relevance
“…Our results also indicated that females present a significantly higher relative frequency in larger size classes, which have been previously reported for P. schmitti populations (Santos et al, 2005(Santos et al, , 2008. Penaeid females are larger than males due to the body space needed for gonadal development (Hartnoll, 1982;Dall et al, 1990) and thus more abundant in larger size classes (García & Le Reste, 1986) Studies of ovarian development in penaeids have been used as a tool for the establishment of guidelines for fishery management (Quintero & Gracia, 1998), as well as the improvement of breeding technology for aquaculture operations (Peixoto et al, 2003;Dumont et al, 2007;Gonçalves et al, 2009;Machado et al, 2009). Histological analyses of the ovaries are considered to be one of the most accurate procedures for the determination of the maturational stage of female crustaceans (Ohtomi et al, 2003;Carbonell et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our results also indicated that females present a significantly higher relative frequency in larger size classes, which have been previously reported for P. schmitti populations (Santos et al, 2005(Santos et al, , 2008. Penaeid females are larger than males due to the body space needed for gonadal development (Hartnoll, 1982;Dall et al, 1990) and thus more abundant in larger size classes (García & Le Reste, 1986) Studies of ovarian development in penaeids have been used as a tool for the establishment of guidelines for fishery management (Quintero & Gracia, 1998), as well as the improvement of breeding technology for aquaculture operations (Peixoto et al, 2003;Dumont et al, 2007;Gonçalves et al, 2009;Machado et al, 2009). Histological analyses of the ovaries are considered to be one of the most accurate procedures for the determination of the maturational stage of female crustaceans (Ohtomi et al, 2003;Carbonell et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Histological analyses of the ovaries are considered to be one of the most accurate procedures for the determination of the maturational stage of female crustaceans (Ohtomi et al, 2003;Carbonell et al, 2006). This approach may guarantee greater reliability for the determination of the maturation stage, given the precision in identification of the different developmental stages and the potential for comparisons with features observed macroscopically, such as the morphology and coloration of the gonad (Quintero & Garcia, 1998;Peixoto et al, 2003;Machado et al, 2009). The stages of ovarian maturation in penaeids have been defined according to the presence or absence of basophilic, vitellogenic, mature, and atretic oocytes (Quintero & Gracia, 1998;Peixoto et al, 2003;Dumont et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations